Adopting a business model perspective for sustainable building - Vasudev, Badi (My University, 2017)
The importance to sustainability in building sector become important mostly because of more energy consumption and usage of resources in construction of buildings. Business models with proper key elements for sustainable buildings has the capability to reduce the negative impact on environment and raise the economic and environmental benefits. But there are many challenges in order to achieve goals, for this a wide research is necessary on both business models and sustainable buildings. Therefore, the aim of the thesis is to investigate business models, sustainable buildings and subtopics related to these tasks and develop a new business model for sustainable buildings with considering different views from both literature and case studies. In order to achieve, a qualitative method with an inductive approach is used to conduct the study. For this, two research methods are used in the process. Firstly, a literature review has been done on following topics such as business models, business model innovation, sustainable buildings and sustainable development. Secondly, from the case study research four case studies are selected and divided into two types those are individual buildings and companies. From the literature and case studies key elements are identified and designed a new business model. The new business model has four main elements: sustainability, innovation, networking and value proposition, and sub elements are: energy efficiency methods and environmental care; design, IT support & tools, and innovative architecture; key stakeholder identification and customer and employee satisfaction; and newness. Sustainable buildings with economic gains are challenging to achieve. However, sustainable buildings add value to the society and economic benefits can be achieved in the long-run. This new business model can be basic guideline for start-ups, small scale companies and for future research.
Keywords: Annan samhällsbyggnadsteknik; Other Civil Engineering